If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 1) + 2(3 + -1x) = 0 Reorder the terms: 3(1 + 3x) + 2(3 + -1x) = 0 (1 * 3 + 3x * 3) + 2(3 + -1x) = 0 (3 + 9x) + 2(3 + -1x) = 0 3 + 9x + (3 * 2 + -1x * 2) = 0 3 + 9x + (6 + -2x) = 0 Reorder the terms: 3 + 6 + 9x + -2x = 0 Combine like terms: 3 + 6 = 9 9 + 9x + -2x = 0 Combine like terms: 9x + -2x = 7x 9 + 7x = 0 Solving 9 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 7x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 7x = 0 + -9 7x = 0 + -9 Combine like terms: 0 + -9 = -9 7x = -9 Divide each side by '7'. x = -1.285714286 Simplifying x = -1.285714286
| (10y^5)+(15y^4)-25y^3=0 | | 2x+35=7 | | 104[2s-5]=108 | | 9x(4X+37)=180 | | 9x+(4X+37)=180 | | am+bx=c | | 5x+4y=-1 | | 6(y+10)+y=2(y+2)+2 | | 5x^2+9x-10=0 | | 14M=11 | | 5/6=c/9 | | 6(y+10)+y=2(y+2)-2 | | 2z-8=3z-7 | | 4z-4=5z | | -3=3x-5 | | 6X+6X+2+9=6X+5+5X | | 8x^2+8x-3=0 | | -5(x+1)=7x-29 | | (x-6)2=7 | | 2+3x=-x | | 2u+v=-8 | | 5x^2+8x-8=0 | | 4(x+5)-2x=5(2x+7)-3x | | -4x-2=5 | | b+3b-1=15 | | 5x^2+5x-5=y | | 3x-3=3(x-8) | | 20x-5(x-1)=0 | | 7a-2=7 | | 70=3x | | (5x-2)2=17 | | x-9=34 |